2021
DOI: 10.3390/ijms22147503
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of the Host Immune Response by Betaherpesviruses

Abstract: The human immune system boasts a diverse array of strategies for recognizing and eradicating invading pathogens. Human betaherpesviruses, a highly prevalent subfamily of viruses, include human cytomegalovirus (HCMV), human herpesvirus (HHV) 6A, HHV-6B, and HHV-7. These viruses have evolved numerous mechanisms for evading the host response. In this review, we will highlight the complex interplay between betaherpesviruses and the human immune response, focusing on protein function. We will explore methods by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 236 publications
(296 reference statements)
0
7
0
Order By: Relevance
“…We next considered that both organelles coordinate immune signaling, with the immune factors MAVS and STING primarily localized to mitochondria and ER, respectively 83 . Several HCMV proteins are known to target and inhibit STING 6 , 84 – 88 . Our microscopy data showed that ER-mitochondria tethering reduced expression of the immediate early viral protein 1 (IE1), a read-out of active HCMV infection 89 , both in total IE1-producing cells and IE1 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next considered that both organelles coordinate immune signaling, with the immune factors MAVS and STING primarily localized to mitochondria and ER, respectively 83 . Several HCMV proteins are known to target and inhibit STING 6 , 84 – 88 . Our microscopy data showed that ER-mitochondria tethering reduced expression of the immediate early viral protein 1 (IE1), a read-out of active HCMV infection 89 , both in total IE1-producing cells and IE1 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A central characteristic of herpesviruses is their ability to maintain life-long infections despite robust antiviral responses from the host. To achieve this, herpesviruses express multiple accessory proteins, many of which are dedicated to the evasion of host restriction factors [ 6 ]. These viral evasion genes display the characteristic evolutionary signatures of ongoing conflict with host defence [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our six-year-old A-T patient with HIGM variant, in whom non-Hodgkin lymphoma (NHL) was diagnosed, showed reactivation of human herpes virus (HHV)-6 but not EBV, which DNA was undetectable. This observation might be supported by studies of the immune response to HHV-6 in T-cell immunodeficient humans failing protection against the reactivation of the virus causing infectious, inflammatory, and malignant lifethreatening complications (52,53).…”
Section: Discussionmentioning
confidence: 90%